(untitled) - O'Neill, Robert (England, 1984)
Kennel Three is a continuation and extension of Kennel Two and also suitable for students who have completed other pre-intermediate course. This teacher's book includes all contents of the student's book interleaved with teaching notes.
Keywords: English language,Ngôn ngữ tiếng Anh